Effects of Humic Acid on Seed Germination and Seedling Growth of Haloxylon Ammodendron Under NaCl Stress - Wang Bin; Li Chengzhi (Shuitu baochi tongbao)
[Objective] The effects of humic acid on seed germination and seedling growth of Haloxylon ammodendron seeds under NaCl stress were studied in order to provide technical supports for ecological restoration in arid mining areas. [Methods] Germination and seedling growth of Haloxylon ammodendron seeds were measured under five NaCl stress concentrations and five humic acid additions. [Results] Application of humic acid at appropriate levels significantly increased seed germination rate, alleviated salt stress during the seed germination, increased the growth of primary roots, and reduced seedling damage caused by salt stress. Under 1.0 mol/L NaCl, humic acid at 700 mg/kg produced the best alleviating effect. For this treatment, germination rate, germination potential, root length, fresh mass of young roots, and dry mass of young roots were 10%, 11.12%, 1.77 cm, 4.84 mg, and 4.03 mg, respectively, greater than observed for the control treatment. [Conclusion] Humic acid can be used as a regulator of seed germination and seedling growth in the ecological restoration of arid mining areas. Humic acid has good potential for use as a regulator of saline soils in arid mining areas.